Simultaneous control for timely decision making in public management, 2022 - Jinchuña Huallpa, Jorge; Fernández Sosa, Luís Enrique; Flores Arocutipa, Javier Pedro (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
Introduction: simultaneous control is a key tool for timely decision making in public institutions. Objective: to determine if simultaneous control contributes to timely decision making in public management, 2022. Methodology: the research used is applied, quantitative approach, non-experimental design of longitudinal cut, descriptive, documentary and relational level, the study population was 108395 simultaneous control reports obtained from the portal of the Comptroller General of the Republic (CGR) from the period 2018 to 2022 of the 3396 entities within the scope of the National Control System (SNC). Documentary analysis technique was applied to 25265 simultaneous control reports, 19275 control visits and 63855 ex-officio orientation, with documentary analysis guide. Interviews were conducted with public managers and officials working in the national control system; the data were processed in SPSS V.26. Results: the control services provided by the Office of the Comptroller General of the Republic (CGR) and the Institutional Control Bodies (OCIs) correspond to simultaneous control 89 % in 2018, 71 % in 2019, 75,2 % in 2020, 67 % in 2021, 71,1 % was oriented to local governments as of June 2022. Public managers corrected (mitigated) on average < 25 %; corrective actions were partly taken to mitigate warned risks. There is an average positive relationship between concurrent control and decision making (Pearson’s coefficient 0,5). Conclusion: it is shown that there is an average positive relationship between concurrent control and timely decision making in public management. Concurrent control, control visit and ex officio guidance contribute in part to timely decision making in public management.